Hubungan Pengetahuan dan Status Gizi Ibu Hamil terhadap Risiko Anemia Ibu Hamil di Puskesmas Kereng Bangkirai - Oktaviani Oktaviani; Lola Meyasa (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
Anemia during pregnancy requires attention due to potential harm mother and infant. Furthermore, it is an increased mother’s risk of the dead. It is suggested that the high rate of anemia is related to the level of knowledge and mothers’ nutrition. The Kereng Bangkirai Health center is one of the basic emergency on neonatal obstetric service, so-called PONED, in Palangka Raya. It is also noticed that pregnant women having lowest number on Fe intake. This research was aimed to analyze the relationship between the level of knowledge and nutrition status on maternity risk in Kereng Bangkirai Health Centre. The research was conducted using a cross-sectional design. The population was all pregnant women within Kereng Bangkirai health center, on which recorded during January, 1st to Dec, 31st 2015 period. The calculated sample was 140 persons, using consecutive sampling technique. Univariate conducted through frequency distribution while bivariate analysis with chi-square. The study indicates that the mothers’ level of knowledge had a significant relationship with anemia (p=0.04). Meanwhile, their nutrition status showed no linkage with anemia. It is concluded that the mothers’ cognition is a risk factor for anemia during pregnancy.